Republic of Bulgaria : Alternative Dispute Resolution for Financial Services Options - World Bank (Washington, DC, 2013)
The objective of this technical note is to evaluate the existing legal, regulatory and institutional framework of financial Alternative dispute resolution body, for example an ombudsman (ADR) mechanisms in Bulgaria, and to present the authorities with options for reform and improvement. There is a need to further strengthen and reform the existing financial ADR framework in Bulgaria. Fortifying the design and structure of financial ADR mechanisms is an important step to increase currently low levels of consumer trust in financial services. In addition, the implementation of the recently approved European Union (EU) Directive on ADR will require a significant amount of restructuring and reorganization of the existing ADR mechanisms in Bulgaria in order to be compliant with the new required standards. An ADR will not be a success unless consumers can be confident that financial services providers will take part and will follow decisions in favor of the consumer. Bearing in mind the Bulgarian context and the limitations imposed by the Bulgarian constitution, it is recommended to opt for a compulsory and binding ADR structure, but with a possibility to appeal to court. Moreover, financial services providers should bear the first-line responsibility for resolving complaints and be subject to similar complaints handling rules and procedures. In order to be successful, the new arrangements for financial ADR need to command respect from financial services consumers, financial services providers and the authorities. Where the views of stakeholders currently diverge, some compromise will be necessary in order to create a coherent and workable system.